Anion-dependent switching: dynamically controlling the conformation of hydrogen-bonded diphenylacetylenes. - Jones, I; Hamilton, A (2011)
With a grain of salt: An anion-dependent switch based on an intramolecularly H-bonded diphenylacetylene is reported. The addition of Cl - causes the conformation of the H-bond acceptor to switch from the urea protons to the amide proton (see scheme; blue N, red O, green Cl), suggesting the use of such systems as fluorescent anion sensors. © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.